2019
DOI: 10.1021/acs.macromol.9b01540
|View full text |Cite
|
Sign up to set email alerts
|

Regioregular-block-Regiorandom Poly(3-hexylthiophene) Copolymers for Mechanically Robust and High-Performance Thin-Film Transistors

Abstract: In this work, we develop mechanically robust and high-performance organic thin-film transistors (OTFTs) based on poly­(3-hexylthiophene) (P3HT) regioblock copolymers (block-P3HTs). These block-P3HTs consist of regioregular (rre) and regiorandom (rra) P3HTs, where the highly crystalline rre block allows efficient charge transport while the amorphous rra block provides mechanical robustness and interdomain connection. To examine the effects of the molecular architecture on the OTFT performance and stretchability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 74 publications
2
57
0
Order By: Relevance
“…Reproduced with permission. 114,115 Copyright 2017, American Chemical Society, and copyright 2019, American Chemical Society. Comparative analysis of directionally rre and rra D-A copolymers demonstrated that the directional RR of the side chains or functional groups exerts an inuence on their light absorption, packing order, and charge mobility.…”
Section: Rr Of D-a Copolymersmentioning
confidence: 99%
“…Reproduced with permission. 114,115 Copyright 2017, American Chemical Society, and copyright 2019, American Chemical Society. Comparative analysis of directionally rre and rra D-A copolymers demonstrated that the directional RR of the side chains or functional groups exerts an inuence on their light absorption, packing order, and charge mobility.…”
Section: Rr Of D-a Copolymersmentioning
confidence: 99%
“…The amounts of edge‐on oriented crystallites were calculated from the integration of the area of the (100) scattering peaks ( A 100 ) along with azimuth angles (Figure 4c). [ 29 ] The edge‐on ratio was gradually increased from 4% (PNDIT2/IM‐0) to 51% (PNDIT2/IM‐0.45). The edge‐on oriented crystallites are beneficial for providing efficient charge‐transport pathways between the electrodes in OFETs.…”
Section: Resultsmentioning
confidence: 99%
“…P3HT is another classical building block in polymer semiconductors. Kim [ 37 ], Son [ 38 ], and Park [ 39 ] synthesized P3HT based IEOSs with different regioregularity (RR) through Grignard metathesis (GRIM) by Kumada coupling; Shen [ 40 ] and Smith [ 41 ] synthesized P3SiT, P3OT, and P3ddT by changing side chains by Kumada coupling. Benzodithiophene (BDT)-based polymers (PBDT-T, PBDT-2T, PBDT-3T, and PBDT-B3T) with different side chains was prepared by Suzuki coupling [ 42 ].…”
Section: Synthetic Methodsmentioning
confidence: 99%